2019
DOI: 10.21776/ub.jam.2019.017.02.11
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP BETWEEN TOTAL QUALITY MANAGEMENT ELEMENT, OPERATIONAL PERFORMANCE AND ORGANIZATIONAL PERFORMANCE IN FOOD PRODUCTION SMEs

Abstract: The system of improvement and quality management has a fairly rapid development to answer the needs of consumers in the future. TQM is a solution to improve quality in the SMEs food industry, which contributes greatly to the developing countries. The purpose of this paper is to explore the relationship between TQM elements consisting of "Soft" and "Hard" aspects, for operational performance and their impact on the performance of SME organizations. Empirical data was taken from 136 SMEs in food production in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 18 publications
(51 reference statements)
6
23
2
1
Order By: Relevance
“…The result concluded that the TQM implementation and JIT will enable the companies to produce a higher quality of product, lower cost and faster lead time Sutrisno, 2019 SME sector The result concluded that TQM are significantly improved operational performance of the company, increase customer satisfaction as well as substantially increased product quality. In the end, it will improve an organization competitive advantage and business sustainability Int.…”
Section: Manufacturing Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…The result concluded that the TQM implementation and JIT will enable the companies to produce a higher quality of product, lower cost and faster lead time Sutrisno, 2019 SME sector The result concluded that TQM are significantly improved operational performance of the company, increase customer satisfaction as well as substantially increased product quality. In the end, it will improve an organization competitive advantage and business sustainability Int.…”
Section: Manufacturing Sectormentioning
confidence: 99%
“…Similarly in Indonesia, Sutrisno (2019) did study in one of SME and concluded that TQM are significantly improved operational performance of the company, increase customer satisfaction as well as substantially increased product quality. These improvement will increase an organization competitive advantage and business sustainability.…”
Section: Manufacturing Sectormentioning
confidence: 99%
“…The research methodology used is quantitative research. Quantitative research studies the relationships between variables in the formulation of the problem set from a phenomenon and sees the possible connection (Sekaran & Bougie, 2016). This research involved all financial section employees at Dr. Saiful Anwar Malang Hospital, which numbered 50 employees as the respondent and gave them a questionnaire for the data collection.…”
Section: Methodsmentioning
confidence: 99%
“…A company with good employee performances will have a good company performance, showing that the existence of a relationship between individual or group performance with company performance is very close. The reason for the decline in employee performance is due to work conflicts (Sutrisno, 2019). The quality of employee performance is closely related to the leader's role in providing direction to subordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Resource Based View. The theory of Resource Base Theory (RBT) in organizations focus on internal factors that influence organizational performance in order to achieve competitive advantage (Sutrisno, 2019), according to Barney (1991), we need to develops as a set of resources that add positive value, is unique, difficult to imitate, and irreplaceable (assets, capabilities, competencies, organizational processes, information, and knowledge). Resource Based Theory can also help companies capture opportunities and neutralize threats.…”
Section: Literature Reviewmentioning
confidence: 99%